A aplicação dos princípios da vedação ao efeito confiscatório e non bis in idem nas sanções tributárias: uma análise a partir da sua natureza jurídica - Veloso, Jade Thomaz (2019)
This is a research on the legal nature of tax sanctions and the possible application of the principles of non bis in idem and prohibition of confiscatory effect. Defining the legal nature of tax sanctions is essential to understand whether tax sanctions should follow the same legal regime as criminal sanctions, whether they should follow the principles applicable to material tax law or whether they are an autonomous branch with its own regime. We list some topics that we consider relevant for this analysis, from the method to be used in the research, elements applicable or not to tax sanctions and finally our study on the applicability of the chosen principles to tax sanctions. The subject is controversial, since the principle of non bis in idem is constantly linked to criminal law, and the principle of prohibition of confiscatory effect is expressly mentioned in the Federal Constitution as to its application to taxes. For this reason, we chose this object theme for our dissertation